Acumulação por espoliação e a integração da América Latina na divisão internacional do trabalho - Barbosa, Eufrasina Campelo Borges Mendonça (2016)
The current economic model exerts strong pressure on the environment. This is the crux of the contradiction between the economy and the ecosystems limits. The productive forces advance driving capital to the world-system condition. It is structured, thus, an international division of the work that involves the national economies in an adequate web to the enlarged reproduction of the capital. Historically, hegemonic countries imposed their interests to consolidate imperial forms of domination and accumulation by dispossession. Peripheral countries, in turn, remain in the condition of commodities producers and financial dependent and technology of the central countries. The study aims to analyze the geopolitical integration process of Latin America, which seeks to provide physical infrastructure and information necessary to facilitate the mobility of trade flows and international finance capital and the likely repercussions on the political and economic sovereignty of the region. This process contributes to weaken the control of States over the management of natural resources. In this scenario, the research aims to answer how the logistics integration contributes to the consolidation of neoextrativista model in Latin America. The methodology is exploratory. From the point of view of the problem approach, the interpretive character classifies this work as essentially qualitative. In addition, it applies to interdisciplinarity because of the need to integrate the frontiers of knowledge, such as sociology, economics, geography, ecology, physics, among others, in order to build a complex unit to be studied. The general conclusion is that logistics infrastructure only facilitate the exportation flow of commodities, which the final product has no significant effect on the local economy.